Aggressive Angiomyxoma - L Padmavathy; L Lakshmana Rao; M Dhana Lakshmi; N Sylvester (Wolters Kluwer Medknow Publications, 2014)
Myxoid tumors are a heterogeneous group of lesions characterized by a marked abundance of extra cellular mucoid (myxoid) matrix. [1] The term aggressive emphasizes the often infiltrative nature of the tumor and its frequent association with recurrence. [2] A case of aggressive angiomyxoma arising from the vagina in a 55-year-old woman is reported for its rarity.